Calcineurin stimulation by Cnb1p overproduction mitigates protein aggregation and α-synuclein toxicity in a yeast model of synucleinopathy - Srishti Chawla; Doryaneh Ahmadpour; Kara L. Schneider; Navinder Kumar; Arthur Fischbach; Mikael Molin; Thomas Nystrom (Cell Communication and Signaling, 2023)
Abstract The calcium-responsive phosphatase, calcineurin, senses changes in Ca2+ concentrations in a calmodulin-dependent manner. Here we report that under non-stress conditions, inactivation of calcineurin signaling or deleting the calcineurin-dependent transcription factor CRZ1 triggered the formation of chaperone Hsp100p (Hsp104p)-associated protein aggregates in Saccharomyces cerevisiae. Furthermore, calcineurin inactivation aggravated α-Synuclein-related cytotoxicity. Conversely, elevated production of the calcineurin activator, Cnb1p, suppressed protein aggregation and cytotoxicity associated with the familial Parkinson’s disease-related mutant α-Synuclein A53T in a partly CRZ1-dependent manner. Activation of calcineurin boosted normal localization of both wild type and mutant α-synuclein to the plasma membrane, an intervention previously shown to mitigate α-synuclein toxicity in Parkinson’s disease models. The findings demonstrate that calcineurin signaling, and Ca2+ influx to the vacuole, limit protein quality control in non-stressed cells and may have implications for elucidating to which extent aberrant calcineurin signaling contributes to the progression of Parkinson’s disease(s) and other synucleinopathies. Video Abstract